Cold Sensitivity in Ulnar Neuropathy at the Elbow - Relation to Symptoms and Disability, Influence of Diabetes and Impact on Surgical Outcome - Zimmerman, Malin; Peyron, Hanna; Svensson, Ann-Marie; Eeg-Olofsson, Katarina; Nyman, Erika; Dahlin, Lars B. (Frontiers in Clinical Diabetes and Healthcare, 2021)
Cold sensitivity, an abnormal response to exposure to cold, is debilitating. It often affects people with nerve injuries and diabetes. Knowledge about the occurrence and prognostic impact of cold sensitivity in people with ulnar neuropathy at the elbow (UNE) is limited. We aimed to investigate the occurrence of cold sensitivity in UNE in relation to disability, the influence of diabetes and impact on surgical outcome. Data concerning 1270 persons operated on for UNE from 2010-2016 from the Swedish National Register for Hand Surgery (HAKIR) were matched with data from the Swedish National Diabetes Register (NDR). Disability and symptoms were assessed preoperatively, and at three and 12 months postoperatively using QuickDASH and a symptom-specific survey (HQ-8) containing one item regarding cold sensitivity. Differences regarding grade of cold sensitivity, occurrence of diabetes, QuickDASH scores and HQ-8 scores were studied. A linear regression analysis was performed to predict surgical outcome based on preoperative cold sensitivity. The mean age of the cases was 52 ± SD 14 years and 48% were women. Preoperatively, 427 answered the questionnaire. Severe cold sensitivity was present in 140/427 (33%) cases, moderate in 164/427 (38%) and mild in 123/427 (29%) cases. Cases with severe preoperative cold sensitivity reported higher QuickDASH scores at all times compared to cases with mild cold sensitivity. Relative change in QuickDASH scores over time did not differ between the groups. Cases with diabetes reported worse cold sensitivity preoperatively, but not postoperatively. All HQ-8 items improved with surgery, but cases with severe cold sensitivity reported worse persisting symptoms. Cold sensitivity is a major problem among those with UNE and an even greater preoperative problem among people with diabetes. It is associated with more symptoms and disability pre- and post-operatively. All cases, regardless of preoperative degree of cold sensitivity improve with surgery.